Resource availability governs polyhydroxyalkanoate (PHA) accumulation and diversity of methanotrophic enrichments from wetlands - Kim, Yujin; Flinkstrom, Zachary; Candry, Pieter; Winkler, Mari-Karoliina H.; Myung, Jaewook (Frontiers in Bioengineering and Biotechnology, 2023)
Aquatic environments account for half of global CH4 emissions, with freshwater wetlands being the most significant contributors. These CH4 fluxes can be partially offset by aerobic CH4 oxidation driven by methanotrophs. Additionally, some methanotrophs can convert CH4 into polyhydroxyalkanoate (PHA), an energy storage molecule as well as a promising bioplastic polymer. In this study, we investigate how PHA-accumulating methanotrophic communities enriched from wetlands were shaped by varying resource availability (i.e., C and N concentrations) at a fixed C/N ratio. Cell yields, PHA accumulation, and community composition were evaluated in high (20% CH4 and 10 mM NH4 + ) and low resource (0.2% CH4 and 0.1 mM NH4 + ) conditions simulating engineered and environmental settings, respectively. High resource availability decreased C-based cell yields, while N-based cell yields remained stable, suggesting nutrient exchange patterns differed between methanotrophic communities at different resource concentrations. PHA accumulation was only observed in high resource enrichments, producing approximately 12.6 ± 2.4% (m/m) PHA, while PHA in low resource enrichments remained below detection. High resource enrichments were dominated by Methylocystis methanotrophs, while low resource enrichments remained significantly more diverse and contained only a minor population of methanotrophs. This study demonstrates that resource concentration shapes PHA-accumulating methanotrophic communities. Together, this provides useful information to leverage such communities in engineering settings as well as to begin understanding their role in the environment.